2017
DOI: 10.1186/s13018-017-0533-z
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of the sliding length of cephalocervical screws to predict the risk of non-union after osteosynthesis: a retrospective analysis of 86 patients with intracapsular femoral neck fractures

Abstract: BackgroundHere, we assessed the prognostic value of the early sliding length (ESL) for predicting the risk of non-union after internal fixation of femoral neck fractures (FNFs) by Dual SC Screws (DSCS).MethodsA retrospective analysis of 86 patients with intra-capsular FNFs was performed. They underwent osteosynthesis by DSCS at our institution between 2008 and 2013 with a minimum follow-up duration of 6 months. Preoperative displacement, fracture reduction quality, ESL of screws at 2 weeks postoperatively, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
1
0
0
Order By: Relevance
“…Of the 53 Garden's Classification Stage I and II fractures treated with the DSCS system, all showed union except one case. 37 Although explicit comparative studies between these implants with Pauwels type III were not found, our results concurred with those of previous articles.…”
Section: Limitationsupporting
confidence: 92%
“…Of the 53 Garden's Classification Stage I and II fractures treated with the DSCS system, all showed union except one case. 37 Although explicit comparative studies between these implants with Pauwels type III were not found, our results concurred with those of previous articles.…”
Section: Limitationsupporting
confidence: 92%